Periodontal Manifestation in a Patient with Kindler Syndrome - Aysegul Sari; Salih Celik (Hindawi Limited, 2021)
Kindler syndrome is a rare subtype of inherited epidermolysis bullosa. A 42-year-old female patient was admitted to our clinic with a complaint of tooth mobility. Multiple hypo- and hyperpigmented macules dissipated all over her body, prominent poikilodermatous changes, xerosis of the skin, and atrophy were seen in the clinical extraoral examination. Intraoral examination showed atrophy of the buccal mucosa, limited oral opening, epidermal tissue easily separated from the connective tissue, painful ulcers of the hard palate, severe periodontitis, and keratosis of the lips. All of the teeth showed mobility. After dermatologist consultation, the diagnosis of the patient was clinically identified as "Kindler syndrome." All of her teeth were extracted due to her progressive periodontal disease and late admission to our clinic. Periodontal treatment might be effective in treating and controlling oral symptoms related to the syndrome and in improving the patient's quality of life.